Fine‐tuning of CD8+ T‐cell effector functions by targeting the 2B4‐CD48 interaction. Issue 6 (22nd March 2016) - Lissina, Anna; Ambrozak, David R; Boswell, Kristin L; Yang, Wenjing; Boritz, Eli; Wakabayashi, Yoshiyuki; Iglesias, Maria C; Hashimoto, Masao; Takiguchi, Masafumi; Haddad, Elias; Douek, Daniel C; Zhu, Jun; et al.
Abstract : Polyfunctionality and cytotoxic activity dictate CD8 + T‐cell efficacy in the eradication of infected and malignant cells. The induction of these effector functions depends on the specific interaction between the T‐cell receptor (TCR) and its cognate peptide‐MHC class I complex, in addition to signals provided by co‐stimulatory or co‐inhibitory receptors, which can further regulate these functions. Among these receptors, the role of 2B4 is contested, as it has been described as either co‐stimulatory or co‐inhibitory in modulating T‐cell functions. We therefore combined functional, transcriptional and epigenetic approaches to further characterize the impact of disrupting the interaction of 2B4 with its ligand CD48, on the activity of human effector CD8 + T‐cell clones. In this setting, we show that the 2B4‐CD48 axis is involved in the fine‐tuning of CD8 + T‐cell effector function upon antigenic stimulation. Blocking this interaction resulted in reduced CD8 + T‐cell clone‐mediated cytolytic activity, together with a subtle drop in the expression of genes involved in effector function regulation. Our results also imply a variable contribution of the 2B4‐CD48 interaction to the modulation of CD8 + T‐cell functional properties, potentially linked to intrinsic levels of T‐bet expression and TCR avidity. The present study thus provides further insights into the role of the 2B4‐CD48 interaction in the fine regulation of CD8 + T‐cell effector function upon antigenic stimulation.